Six-Month Utilization of Psychotherapy by Older Adults with Depressive Symptoms - Gum, Amber M. (2014)
We explored psychotherapy utilization patterns for community-dwelling older adults with depressive symptoms identified during a statewide initiative designed for identifying risk of substance misuse. Individuals screening negative for substance misuse, but positive for depressive symptoms, agreed to participate in monthly interviews conducted over 6 months (n = 144). Results showed that 39 (27 %) received psychotherapy, of which nearly two-thirds reported four or fewer visits. Mental health counselors were the most frequently reported service providers (50–62.5 %). Location of service varied considerably. This study documents low rates of psychotherapy use and few visits. Current efforts to increase psychotherapy access are discussed.